Micronutrient Intake of Vegans Living in Christchurch, New Zealand - Zane Stankuna; Maria Anna Choukri (Proceedings, 2019)
Background: The two main motives for individuals to exclude all animal-derived products fromtheir diet are health reasons and ethical belief [...]